2019
DOI: 10.3390/genes10121007
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity of Common Sequence Types of Listeria monocytogenes Isolated from Ready-to-Eat Products of Animal Origin in South Africa

Abstract: Listeria monocytogenes is a highly fatal foodborne causative agent that has been implicated in numerous outbreaks and related deaths of listeriosis in the world. In this study, six L. monocytogenes isolated from ready-to-eat (RTE) meat products were analysed using Whole Genome Sequencing (WGS) to identify virulence and resistance genes, prophage sequences, PCR-serogroups, and sequence types (STs). The WGS identified four different STs (ST1, ST121, ST204, and ST876) that belonged to serogroup 4b (lineage I) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 63 publications
4
18
2
Order By: Relevance
“…In the present study, several intact prophages were detected. Similar results were previously obtained by Matle et al [ 54 ], who found almost the same phages among L. monocytogenes isolated from food in South Africa. Such prophage sequences were also reported in strains associated with survival evolution and persistence of L. monocytogenes in food-processing facilities [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, several intact prophages were detected. Similar results were previously obtained by Matle et al [ 54 ], who found almost the same phages among L. monocytogenes isolated from food in South Africa. Such prophage sequences were also reported in strains associated with survival evolution and persistence of L. monocytogenes in food-processing facilities [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, the genes responsible for resistance to fosfomycin, quinolones, sulphonamides, and lincosamides were identified. These molecular markers were often detected also in L. monocytogenes by other authors [ 26 , 34 , 46 , 54 ]. It has been previously described that L. monocytogenes and other Listeria species are characterized by a low resistance to antimicrobials [ 36 , 41 ].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The LIPI-3 pathogenic island, characteristic for L. monocytogenes hypervirulent clones, was identified in only one strain belonging to the IVb serogroup. It was previously shown that this gene cluster was strongly associated with IVb strains, which was also confirmed in the current study, although only one such isolate was identified [ 32 ]. Furthermore, it has also been described that hypervirulent L. monocytogenes strains were connected with the presence of LIPI-4, which was not found in any of the examined isolates [ 14 , 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Several sequences encoding the presence of prophages were detected among 28 L. monocytogenes isolates tested, including intact, questionable, or incomplete molecular markers ( Table S4 ). These prophages were originated from different Listeria phages such as LP101, A006, and LmoS188, and were commonly found in Listeria strains by other authors [ 32 , 50 ]. It has been previously described that the presence of prophage genes in L. monocytogenes had an influence on bacterial virulence and their persistence in food processing environments as well as intracellular survival in the human host [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%